Effect of Thinning and Harvest Type on Storage and Losses of Phosphorous in Pinus taeda L. Plantations in Subtropical Argentina - Rodolfo Andrés Martiarena; Jorge Luis Frangi; Martín Alcides Pinazo; Alejandra Von Wallis; Roberto Antonio Fernández (International Journal of Forestry Research)
The aim of this study was to evaluate the effect of thinning intensity and different harvest types on ecosystem P conservation in 20-year-old Pinus taeda plantation ecosystems at Misiones province, Argentina. The plantation was established in 1985, thinned at three intensities—0, 33, and 66% of basal area of control plots removed by thinning—and harvested in 2005. The nutrient content at harvest was determined for tree, shrub, and herb layers, the forest floor and upper mineral soil. Two harvest types were simulated: stem only and whole tree. Total P content was 56.8, 46.8, and 38.6 kg· ha−1 for 0, 33, and 66% thinning, respectively. Total P exported by harvest was different among treatments, the highest at 0% thinning treatment. Phosphorus stability index values indicated that the P most conservative management option is 66% thinning, harvest of stem only and retention of forest floor, understory, and harvest residues.